A systematic review on the emerging fungal pathogen Neoscytalidium causing infections worldwide (2025)
Scytalidiosis is a dermatomycosis caused by fungi of the genus Neoscytalidium. An increase in the number of cases at the global level has been reported. In the present study, the clinical characteristics of patients diagnosed with scytalidiosis were analyzed through a systematic review of cases reported in the literature. An advanced search was conducted through four databases: MEDLINE/PubMed, SCOPUS, Embase, and SciELO using the terms “Neoscytalidium” or “Scytalidium”. A total of 155 reports with 5,097 cases were analyzed of which 30.12% were women and 27.31% were men. A total of 37 countries reported cases of scytalidiosis. The USA, Thailand, France, Brazil, Colombia, and the UK had the highest number of cases. The most prevalent species were N. dimidiatum (38.96%) and N. hyalinum (7.47%). One case of N. oculus sp. nov. and seven instances of N. novaehollandiae were also reported. Regarding the clinical presentation, 68.30% of patients had onychomycosis, 5.93% had skin infections, and 24.16% presented both types of infections. Other less frequent presentations (1.61%), including keratitis/endophthalmitis, CNS infection, invasive or disseminated infection, sinusitis/rhinosinusitis, mycetoma, endocarditis, and dyskeratosis were also reported. This review shows that the epidemiology of scytalidiosis is changing, other regions that had not been considered endemic are now reporting the highest number of cases. Neoscytalidium spp. should be considered an important emerging pathogen and the main non-dermatophyte fungus causing onychomycosis and skin infections after dermatophytes. Likewise, other clinical presentations caused by this fungal pathogen should not be underestimated, especially in patients with some immunocompromise or underlying disease.